Plurilingual and Intercultural Education in the Mediterranean Countries. - Samra Choubane (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
This paper tacklesthe rich cultural diversity in the Mediterranean countries (case of Algeria) that raises a number of key issues that we may encounter in our day-to-day business. The implementation of a plurilingual and intercultural education involves implications for the educational curriculum. It can have different forms according to context; depending on the language is cooling, the rule of the first foreign language, or the possible position of languages that are present in the school without being taught. It also depends upon varying conditions of feasibility and implementation, and the central or local institutional level, for the institution itself, in the classroom, and with respect to relations between the school and its environment. It also has an impact quite evidently on the training of teachers. These different aspects are addressed in other documents of the platform.